Biofunctionalization of cardiovascular stents to induce endothelialization: Implications for in- stent thrombosis in diabetes - Marei, Isra; Ahmetaj-Shala, Blerina; Triggle, Chris R. (Frontiers in Pharmacology, 2022)
Stent thrombosis remains one of the main causes that lead to vascular stent failure in patients undergoing percutaneous coronary intervention (PCI). Type 2 diabetes mellitus is accompanied by endothelial dysfunction and platelet hyperactivity and is associated with suboptimal outcomes following PCI, and an increase in the incidence of late stent thrombosis. Evidence suggests that late stent thrombosis is caused by the delayed and impaired endothelialization of the lumen of the stent. The endothelium has a key role in modulating inflammation and thrombosis and maintaining homeostasis, thus restoring a functional endothelial cell layer is an important target for the prevention of stent thrombosis. Modifications using specific molecules to induce endothelial cell adhesion, proliferation and function can improve stents endothelialization and prevent thrombosis. Blood endothelial progenitor cells (EPCs) represent a potential cell source for the in situ-endothelialization of vascular conduits and stents. We aim in this review to summarize the main biofunctionalization strategies to induce the in-situ endothelialization of coronary artery stents using circulating endothelial stem cells.